The evaluation of public toilet provisions towards the equitable accomodation of women in selected bus transportation terminals in Quezon City - Sayson, Gabrielle Gay P.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
This study evaluated the provisions, facilities, and amenities inside the women's public restrooms in selected bus transport terminals in Quezon City. If focused on how women's needs are addressed based on their mobility, productivity, and safety towards the equitable, sensible, and appropriate accommodation. The study employed a qualitative research approach which involved a survey of 50 respondents using semi-structed questionnaires to determine the needs of women; on-site observations; and photo documentation of women's toilet in four (4) bus stations to record which amenities and facilities exist on site. Key informant and respondent interviews were conducted to support and validate themes which emerged during the initial data collections. The findings of the study suggested that woman crucially have gender-specific needs which require a specific kind of accommodation in public toilets facilities because females have more biological reason for needing so. Females undergo menstruation and pregnancy; women urinate sitting down and, use toilet paper, and must enter a confined cubicle ; female clothing is a lot more complicated than men; women often have purses to situate; and female brings small children in the stall with them. However, toilet amenities in the local bus stations are lacking and remain unkempt because of insufficient planning, lack of budget allocation and prioritization, poor enforcement and regulation, and the influence of certain cultural practices. Involving women and actual users of the space in the course of planning, designing and implementing provisions for public toilet allows users to contribute first hand experiences regarding the utilization of the public restroom and shall ensure the effectivity of the guidelines.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Public toilets -- Philippines -- Quezon City; Women's restrooms -- Philippines -- Quezon City; Restrooms -- Philippines -- Quezon City